The use of epigraphic inscriptions in pottery - Akhmedov Ravshan Tolkunovich (Genius Journals, 2022)
This article provides detailed information on the importance and application of epigraphic inscriptions in Central Asian pottery
Keywords: calligraphy; ceramics; epigraphy; monograph